Sylvia Plath: Her Growth Beyond Electra Complex: A Study of Her Poem ''Daddy'' - Chhetri, Narendra Bahadur (Butwal Campus Journal, 2023)
Sylvia Plath is a great poet from America in the 20th century. Although she is known as a talented woman poet, she is said to have been unfit to adjust herself in the society due to mismatch between her aspirations and societal expectations from her. The society expected her to settle down into a family by marrying a man, and giving birth to his children. On the other hand, she wanted to build her career in writing. She didn't want to give in to the pressures of the society. However, she couldn't go against the conventions of the society for long. The pressure from the society was too much upon her. She is said to have undergone the experience of close emotional attachment to her father who had died when she was just eight. Some of her works including the poem under study show a girl-child's strong emotional attachment towards her father. The present research work has made an attempt at exploring the theme of Electra Complex in her poem Daddy.